Schizophyllum commune (Fries) mushroom: a review on its nutritional components, antioxidative, and anti-inflammatory properties - Abd Razak, Dang Lelamurni; Abd Ghani, Amsal; Mohd Lazim, Mohd Izwan; Khulidin, Khairul Asfamawi; Shahidi, Fereidoon; Ismail, Amin (Elsevier, 2024)
The compelling health-promoting properties of mushrooms have attracted researchers to explore Schizophyllum commune as a source of food and pharmaceutical products. A systematic review was conducted by searching specific electronic databases for relevant articles on nutritional, antioxidative, and anti-inflammatory properties of S. commune. Significant advances have been achieved in the antioxidative properties of S. commune as a consequence of studies involving cell and animal models, and the identification of mechanisms of action through molecular studies. However, its anti-inflammatory properties are meagerly reported and research on the nutritional properties of S. commune is deficient. It is anticipated that insights about these developments will motivate further discovery of novel antioxidative and anti-inflammatory components, and advance research on the nutritional properties of S. commune.